INFLUENCE OF ONLINE GAMES ON STUDENT ACHIEVEMENT OF TRI KARYA SUNGGAL SMK - sibarani, leonardo; mawati, Rah (ELT (English Language Teaching Prima Journal), 2023)
The development of the times makes it easy for humans to carry out their activities. Thedevelopment of the times affects various fields of technology and entertainment, one of thedevelopments in the field of technology and entertainment is the large number of online gamesthat can be found both on websites and on Android bases. Online games are games that areplayed online or using the internet network, online games can be easily found in internet cafesand mobile phones, so everyone can easily access them, both children and adults can play them.Online games have two impacts, namely good and bad. The good impact is to entertain its users.The bad impact is that many users forget the time, so they forget to do their work. This is provenby the results of this study, statistical test results with SPSS on variable X1 (online game),obtained a calculated value = 17.040 and a significance of 0< 5% so that Ho was rejected. Thismeans that the variable of influence of online games has an influence.Keywords :Online Games and Learning Achievement